Perlindungan Hukum terhadap Konsumen bagi Pengguna Kosmetik Ilegal yang Diiklankan Influencer di Media Sosial - Ni Putu Gita Padmayani; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Warmadewa Press, 2022)
This study aims to discuss forms of legal protection for consumers and the responsibility of influencers against consumer losses for illegal cosmetic products advertised on social media. Current technological developments make many business actors market cosmetic products using the services of influencers on social media. However, it is not uncommon for influencers to promote illegal cosmetic products that do not have distribution permits. This type of research includes normative legal research that uses a statutory approach and analysis of legal concepts. The results of the study indicate that the form of legal protection for consumers for the use of illegal cosmetic products refers to Article 1365 of the Civil Code, Article 4 of Law No. 8 of 1999 concerning Consumer Protection, Article 9 of the ITE Law and Article 378 of the Criminal Code, then Responsibilities influencers on illegal cosmetics advertised on social media can be based on Law No. 8 of 1999 concerning Consumer Protection and Article 1365 of the Civil Code. For this reason, the government should further reaffirm the regulations regarding the protection of consumers and an influencer who advertises a product should have good intentions in carrying out his profession.